The Phenomenon of Land Sale and Purchase Practices Without Land Deeds - Lune, Nur Dilang W; Dungga, Weny Almoravid (Universitas Negeri Gorontalo, 2023)
This study aims to determine the phenomenon of land sale and purchase practices without land deeds. The research method used is empirical research method. The results obtained show that one of the problems that often occurs in buying and selling transactions as an activity of transferring land rights is buying and selling land without a certificate. In fact, land certificates are valid and strong evidence of land ownership as stated in Article 19 Paragraph 2 Letter c of the UUPA. Factors causing this practice include legal, economic, social, and administrative factors. Slow and confusing processing of land certificates, lack of availability of land with legal status, the high cost of processing land certificates, lack of supervision from the community and government, and lack of public awareness and attention.